Combining policy analyses, exploratory scenarios, and integrated modelling to assess land use policy options. Issue 94 (April 2019) - Hauck, Jennifer; Schleyer, Christian; Priess, Jörg A.; Veerkamp, Clara J.; Dunford, Rob; Alkemade, Rob; Berry, Pam; Primmer, Eeva; Kok, Marcel; Young, Juliette; Haines-Young, Roy; Dick, Jan; et al.
Highlights: Subsidies for technology-driven intensification of agriculture are widely considered. Negative effects of subsidies to promote biomass production can be mitigated. An integrated Ecosystem Services Framework is a promising policy option. Alternatives include rural development approaches for agricultural extensification. Abstract: Scenario-based approaches provide decision makers with accessible storylines of potential future changes. The parameterisation of such storylines as input variables for integrated assessment models allows using models as a test bed for assessing the effects of alternative land use policy options in different scenarios. However, the potential of this kind of policy-screening analysis can be further improved by assessing the institutional compatibility of the policy options under review. The aim of this paper is to explore the added value of combining institutions-oriented policy analyses with scenario-modelling approaches for improved assessments of EU land use policy options. We describe an expert-based, stepwise process to combine four scenario storylines and two integrated assessment model approaches (CLIMSAVE & IMAGE-GLOBIO) with a procedure for institutional compatibility assessment. Among the subsidies we assessed were those for technology-driven intensification of agricultural production, which would contribute to decreasing demand for cropland across a range of scenarios. In regionalised policy designs, they also contribute to ecological effectiveness, and higher costs of governing. Subsidies to promote biomass production can have negative effects on ecosystems including land conversion, conversion of grassland into cropland as well as conversion of natural forests into managed forests. These effects can to some extent be mitigated by careful policy design which considers the institutional context and features cross-sectoral coordination. An integrated Ecosystem Services Framework policy could accommodate regionalised policy designs and cross-sectoral coordination, however, it can operate only under specific circumstances and needs particular efforts. Rural development approaches are another alternative which feature expansion of cropland by means of a large-scale, bottom-up transformation based on voluntary changes in behaviour, flexibility, participation, and local and regional collaboration. Apart from a vast number of interdisciplinary lessons learned, we also gained insights from the science-policy interface. A weak EU appeared as a plausible scenario from a scientific perspective, given the current political environment. However, it appreaded to be unacceptable at EU level policy making. We decided to maintain scientific independence and looked at policy options also in the context of a weak EU yielding environmentally beneficial opportunities for regional decision making at the expense of relevance of our scenarios to EU level policy makers.